ANALYSIS OF PHYSIOLOGICAL (PAO2, PULSE AND BLOOD PRESSURE) CHANGES DURING MODIFIED ECT UNDER GENERAL ANAESTHESIA: Physiological Changes in Modified ECT - Shah, Mubashar; Shah, Hamid Ali; Mustafa, Ghulam; Shah, Farrukh Saleem; ., Zaffar; ., Sheraz; ., Kashif (Pakistan Armed Forces Medical Journal, 2015)
Objective: To study the changes in physiological parameters ie PAO2, pulse and blood pressure changes during ECT under GA. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Psychiatry and Department of Anaesthesiology, Combined Military Hospital Abbottabad from Sep 2009 to Feb 2010. Patients and Methods: A total of 50 patients with depression were given four separate ECT sessions each. All patients were anaesthetized using propofol 180-200 mg I/V and suxamethonium 50 mg ie 0.75-1 mg per kg I/V without atropine. They were stratified according to physiological changes including PAO2, pulse and blood pressure at 1, 2 and 5 min after ECT. Oxygen saturation was measured using a pulse oximeter, which measures saturations in the range of 65-100%. Results: Age range was 19-65 years; mean 46 years (SD±13). Mean diastolic BP before ECT was 84.72 that decreased post ECT ie 78.02 and 77.46 and 74.44 at interval of 1, 2 and 5 minute respectively. Post-ECT pulse and PAO2 behaved similarly. Post ECT systolic BP decreased at 1and 5 minutes. Pulse rate decreased after ECT. Conclusion: ECT under propofol is one of the most effective and safe modality of treatment for psychiatric patients under the supervision of qualified psychiatrists and anaesthesiologists and it gives more stable hemodynamic changes.